The association between social support and psychological factors with health-promoting behaviours in pregnant women: A cross-sectional study - Nasrin Rashan; Nasibeh Sharifi; Azita Fathnezhad-Kazemi; Khadijeh Golnazari; Safoura Taheri (Wolters Kluwer Medknow Publications, 2021)
INTRODUCTION: Health promotion is one of the most important aspects in pregnancy, and health-promoting behaviors are one of the major determinants of health under the influence of various factors. This study aimed to determine the association between social support and psychological factors with health-promoting behaviors in pregnant women. MATERIALS And METHODS: This cross-sectional was performed on 375 pregnant women when they had 24-28 weeks in Ilam, October 2018 to May 2019. Two-stage cluster sampling was performed after checking the inclusion criteria. Data collection tools consisted of four questionnaires that were completed in self-report form. The collected data were analyzed by the descriptive and inferential tests with the SPSS software version 19. RESULTS: The mean score of health-promoting behaviors was 139.87 (21.26) and self-healing and physical activity had the highest and the lowest mean 27.67 (4.84) and 16.29 (4.84), respectively. Linear regression analysis showed a significant difference between different level of stress, anxiety, depression, and social support with health-promoting behaviors (P < 0.001). The results showed that one-point increase in the score of stress, anxiety, and depression led to the 2.2%, 6.1%, and 24.1% reduction of health-promoting behaviors, respectively, and one-point score increase in social support resulted in 40% increase in health-promoting behaviors (P < 0.001). CONCLUSION: A negative association was found between psychological factors and a positive relationship with health-promoting behaviors. Although perceived moderate health promotion behaviors and perceived social support were moderate, they did not have a good status in terms of psychological factors. Given awareness of the issues under study in each region is essential and planning to improve stress, anxiety, and depression, as well as promoting and correcting inappropriate behaviors through planned interventions are required.